Pengaruh Reward, Punishment, Pengembangan Karir Terhadap Produktivitas Kerja Pada Pegawai Se-Kecamatan Batu Aji Dengan Motivasi Sebagai Variabel Intervening - Parmadhie Putra, Ongky; E Rumengan , Angelina; Friadi, John (Program Studi Manajemen FEBM UMRAH, 2025)
Employee work productivity at the sub-district level has a very important role in increasing the efficiency and effectiveness of public services. Increased productivity not only impacts short-term performance but also contributes to the development of organizational capacity in the long term. With more productive employees, government agencies can manage resources better and respond to community needs more quickly and effectively. The method used in this study is a quantitative method. Based on the above, a conclusion can be made in this study that Reward has a direct and significant effect on work productivity. Punishment has a direct and significant effect on work productivity. Career development does not have a significant effect on work productivity. Motivation has a direct and significant effect on work productivity. Reward does not have a significant effect on motivation. Punishment does not have a significant effect on motivation. Career development has a significant effect on motivation. Reward does not have a significant effect on work productivity through motivation. Punishment through motivation has no significant effect on work productivity, and career development through motivation has a significant effect on work productivity.